Multilevel dynamics of the UK's EU exit: identity, territory, policy and power. Issue 9 (2nd September 2021) - Wincott, Daniel
ABSTRACT: Introducing a multidisciplinary special issue on the multilevel dynamics of the UK's exit from the European Union (EU), this article considers social science 'impact' from Brexit-related research, including the Economic and Social Research Council's (ESRC) UK in a Changing Europe initiative and Governance after Brexit programme. The issue draws on the initiative's Brexit Priority Grant programme, bringing together economists, political scientists, policy analysts and socio-legal scholars. It analyses the UK's regional and devolution-related Brexit dynamics. The article considers the potential and challenges of cross-disciplinary work and concludes with a critical analysis of Boris Johnson administration's 'levelling up agenda' in a post-Brexit and Covid/Covid-recovery context.